INCREASING THE SECURITY OF GOVERNMENT INFORMATION RESOURCES AT THE EXPENSE OF USING THE THREAT INTELLIGENCE PLATFORM - Zhylin, Artem; Nikolaenko, Bohdan; Bakakynskyi, Oleksandr (Ukrainian Information Security Research Journal, 2022)
With the development of information technology, the need to solve the problem of information security has increased, as it has become the most important strategic resource. At the same time, the vulnerability of the modern information society to unreliable information, untimely receipt of information, industrial espionage, computer crime, etc. is increasing. In this case, the speed of threat detection, in the context of obtaining systemic information about attackers and possible techniques and tools for implementing cyberattacks in order to describe them and respond to them quickly is one of the urgent tasks. In particular, there is a challenge in the application of new systems for collecting information about cyber events, responding to them, storing and exchanging this information, as well as on its basis methods and means of finding attackers using integrated systems or platforms. To solve this type of problem, the promising direction of Threat Intelligence as a new mechanism for gaining knowledge about cyberattacks is studied. Threat Intelligence in cyber security tasks is defined. The analysis of cyberattack indicators and tools for obtaining them is carried out. The standards of description of compromise indicators and platforms of their processing are compared. The technique of Threat Intelligence in tasks of operative detection and blocking of cyberthreats to the state information resources is developed. This technique makes it possible to improve the productivity of cybersecurity analysts and increase the security of resources and information systems.